On the role of singlet versus triplet excited states in the uncaging of ortho-nitrobenzyl caged compounds - Mewes, Jan-Michael; Dreuw, Andreas (Physical chemistry, chemical physics, 2013)
Ortho-Nitrobenzylacetate (oNBA) is one of the smallest caged-compounds utilizing the famous ortho-nitrobenzyl caging group and thus serves here as a proto-typical example. Crucial for efficient uncaging of, here, acetate from oNBA is the formation of the aci-form of the nitro-group, which can be formed via excited-state intramolecular hydrogen transfer (ESIHT) in the lowest excited singlet S1 or the triplet T1 state. Using state-of-the-art quantum chemical methods, the efficiency of singlet and triplet ESIHT in aci-formation is investigated and the results are discussed in comparison to previous calculations on related caged-compounds as well as with respect to recent experimental findings.
Gesehen am 14.12.2017